2006
DOI: 10.1590/s0102-86502006000900003
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do efeito do extrato hidroalcoólico de Schinus terebinthifolius Raddi (Aroeira) no processo de cicatrização da linea alba de ratos

Abstract: OBJETIVO: Avaliar o processo de cicatrização da parede abdominal de ratos após a injeção intraperitoneal do extrato hidroalcóolico de Schinus terebinthifolius Raddi. MÉTODOS: Utilizaram-se 40 ratos da linhagem Wistar, distribuídos em dois grupos de 20 animais, cada um subdividido em dois subgrupos. Estes ratos foram mortos no 3º e 7º dias após a aplicação intraperitoneal do extrato. No grupo experimento, injetou-se uma única dose de extrato hidroalcoólico de Aroeira (100 mg por quilo de peso do animal) e no gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 6 publications
(5 reference statements)
2
12
0
2
Order By: Relevance
“…We also observed an increased wound angiogenesis in STRO-treated mice when compared with Vehicle-treated group. In accordance, our group reported the angiogenic effects by Schinus terebinthifolius Raddi in wound repair 1,28 . However, further studies are necessary to determine possible mechanisms.…”
Section: ■ Discussionsupporting
confidence: 71%
“…We also observed an increased wound angiogenesis in STRO-treated mice when compared with Vehicle-treated group. In accordance, our group reported the angiogenic effects by Schinus terebinthifolius Raddi in wound repair 1,28 . However, further studies are necessary to determine possible mechanisms.…”
Section: ■ Discussionsupporting
confidence: 71%
“…The rat has been widely used because of the anatomical and biological similarities between its abdominal wall and that of humans; it was, therefore, the right choice for this study 6,7 . Various studies have reported that it is easier to anesthetize and operate on Wistar rats in experimental studies 19 , which corroborates the use of this rat strain in the present study.…”
Section: -Acta Cirúrgica Brasileira -Vol 23 (4) 2008supporting
confidence: 91%
“…The healing of the abdominal aponeurosis follows the same principles as those of other mesenchymal tissues; however, the abdominal aponeurosis has limited blood supply and, because of this, limited healing potential 19 .…”
Section: -Acta Cirúrgica Brasileira -Vol 23 (4) 2008mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies on the composition of plant parts, isolated compounds such as: essential oils, flavonoids, fractions enriched of flavonoids, Shinol (flavonoid) and masticadienoic acid, biflavonoids isolated and triterpenes. Have been studied the morphology and anatomy of the seed, barks and leaves, chemical and microscopic examination of the plant, barks development and fruits development, even clinical drug trials (phase I) of an herbal compound (Schinus, Plectranthus and Eucalyptus) 1,3,4,5,7,8,9,10,11,15,18,19,20,21,23,25,26,28,30,31,32,33,34 .…”
mentioning
confidence: 99%